2015
DOI: 10.5811/westjem.2015.1.24150
|View full text |Cite
|
Sign up to set email alerts
|

Change in Intraocular Pressure During Point-of-Care Ultrasound

Abstract: IntroductionPoint-of-care ocular ultrasound (US) is a valuable tool for the evaluation of traumatic ocular injuries. Conventionally, any maneuver that may increase intraocular pressure (IOP) is relatively contraindicated in the setting of globe rupture. Some authors have cautioned against the use of US in these scenarios because of a theoretical concern that an US examination may cause or exacerbate the extrusion of intraocular contents. This study set out to investigate whether ocular US affects IOP. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…If there is a possibility of globe rupture, a thick layer of gel should be used to prevent contact between the eyelid and transducer. A study of 40 patients demonstrated small, transient elevation in intraocular pressure during ocular POCUS, but pressure change was similar to that caused by physical exam [88]. …”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%
“…If there is a possibility of globe rupture, a thick layer of gel should be used to prevent contact between the eyelid and transducer. A study of 40 patients demonstrated small, transient elevation in intraocular pressure during ocular POCUS, but pressure change was similar to that caused by physical exam [88]. …”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%
“…however, more research is needed to determine the role of color flow and pulsed wave doppler in OCS and traumatic retrobulbar hemorrhage. 62 and the use of a plastic shield may further diminish any increases in IOP. 63 In a clinical review based on 8 cases of globe rupture, ultrasound had 100% sensitivity and 99% specificity, 64 whereas an animal model reported 79% sensitivity and 51% specificity.…”
Section: Pitfall #3 -Overreliance On Imagingmentioning
confidence: 99%